Specific storage of glycoconjugates with terminal α-galactosyl moieties in the exocrine pancreas of Fabry disease patients with blood group B - Rybová, Jitka; Kuchar, Ladislav; Hulková, Helena; Asfaw, Befekadu; Dobrovolný, Robert; Sikora, Jakub; Havlícek, Vladimír; Škultéty, Ludovít; Ledvinová, Jana (Glycobiology, 2018)
Blood group B glycosphingolipids (B-GSLs) are substrates of the lysosomal alpha-galactosidase A (AGAL). Similar to its major substrate-globotriaosylceramide (Gb3Cer)-B-GSLs are not degraded and accumulate in the cells of patients affected by an inherited defect of AGAL activity (Fabry disease-FD).The pancreas is a secretory organ known to have high biosynthesis of blood group GSLs. Herein, we provide a comprehensive overview of the biochemical and structural abnormalities in pancreatic tissue from two male FD patients with blood group B. In both patients, we found major accumulation of a variety of complex B-GSLs carrying predominantly hexa- and hepta-saccharide structures. The subcellular pathology was dominated by deposits containing B-glycoconjugates and autofluorescent ceroid. The contribution of Gb3Cer to the storage was minor. This abnormal storage pattern was specific for the pancreatic acinar epithelial cells. Other pancreatic cell types including those of islets of Langerhans were affected much less or not at all.Altogether, we provide evidence for a key role of B-antigens in the biochemical and morphological pathology of the exocrine pancreas in FD patients with blood group B. We believe that our findings will trigger further studies aimed at assessing the potential pancreatic dysfunction in this disease.
Keywords: Fabryho nemoc; beta-buňky; Acinar Cells; Galactose; Pancreas; galaktosa; Male; ABO Blood-Group System; ABO systém krevních skupin; Middle Aged; mužské pohlaví; studie případů a kontrol; glykosfingolipidy; Fabry Disease; Glycosphingolipids; Humans; Insulin-Secreting Cells; lidé středního věku; acinární buňky; pankreas; lidé; Case-Control Studies